An in situ powder diffraction cell for high‐pressure hydrogenation experiments using laboratory X‐ray diffractometers. (1st February 2015) - Moury, Romain; Hauschild, Klaus; Kersten, Wolfgang; Ternieden, Jan; Felderhoff, Michael; Weidenthaler, Claudia
<x xml:space="preserve">Abstract</x> An in situ diffraction cell is presented which has been designed and constructed for in‐house powder diffraction experiments under high gas pressures up to 30 MPa. For a proof of principle, the in situ cell has been tested for several hydrogenation experiments under elevated pressures and temperatures. LaNi5 was chosen as an example for hydrogenation, applying simultaneously 5.5 MPa H2 pressure at a temperature of 423 K. For testing the high‐pressure–temperature suitability of the in situ cell, pressure–temperature experiments up to 14 MPa at 373 K were performed, studying the rehydrogenation of NaH and Al to NaAlH4. The experimental setup enables recording of in situ X‐ray diffraction data on laboratory instruments with short data acquisition times at elevated hydrogen pressures and temperatures.